Giving Exclusive Breastfeeding and Maternal Gestational Age Affects the Developmental Delay of Children Aged 3-36 Months - Hijrianti Rumalean; Yanuarita Tursinawati; Galuh Ramaningrum (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
Developmental disorders can affect one or more areas of development such as gross motor, fine motor, speaking/using language, and social personality/independence. Factors that influence the development in children can come from internal factors (exclusive breastfeeding, and maternal gestational age) and external factors (maternal age and number of children under five in the family). Early detection of development is very important using the Developmental Pre-Screening Questionnaire or DENVER II. The objective of the study is to identify risk factors that influence delays in the development of children aged 3-36 months. This research is an analytic observational with case control approach. The research location was at Integrated Healthcare Unit, Primary Health Center of Rowosari, Semarang. The total sample of this study was 62 in children aged 3-36 months whose development was analyzed using the Developmental Pre-Screening Questionnaire instrument. The sampling technique used purposive sampling. The variables of this study were exclusive breastfeeding, gestational age, maternal age and the number of children under five in the family. Statistical tests used Chi-Square to analyze the relationship between internal and external factors with the delay in child development. The results show that exclusive breastfeeding (p=0.042) and gestational age (p=0.042) have a significant relationship with the development of children aged 3-36 months, while maternal age factors during pregnancy (p=0.425) and number of children under five (p=0,353) have no significant relationship. Thus, internal factors such as exclusive breastfeeding and maternal gestational age affect the developmental delay of children aged 3-36 months.